Influence of annealing temperature on structural and optical properties of SnS:Ag thin film for solar cell application - J.Hamood, Farah; M.hadi, Qunoot; Haneen Abass, Khalid; Khudhur Mohammed, Musaab (International Journal of Engineering and Technology, 2018)
Thermal evaporation method have been used to prepared thin films from tin sulfide (SnS) doping with 20 nm particle size of silver (Ag) at room temperature, under pressure up to 1 × 10-7 mbar with rate of statement 0.5 nm. sec-1. The SnS:Ag thin films deposited on glass substrate at different annealing temperature (as-deposited, 423, 473, 573 and 623 K) for 2 hours. The effect of annealing treatment on the structural and optical properties has been studied. From X- ray diffraction (XRD) examination, predominant peak (111) appears at annealing temperature 623 K, also the others as (101) and (002). Scherer’s formula used to calculate the crystallite size that ranged from 3-7 nm. Using UV-Vis spectrophotometer to recording the transmittance spectra and then calculate the optical properties in the wavelength range 300-900 nm. The absorbance decreased with the increasing of annealing temperature, while the transmittance increased. The optical constants such as refractive index, extinction coefficient, real and imaginary parts of dielectric constant, and absorption coefficient decreased with the increasing of annealing temperature. The energy band gap increased from 2.1 eV for the as- deposited film to 3.3 eV for the film annealed at 623 K.